16-month outcomes following hybrid ablation for long-standing persistent atrial fibrillation in patients with dilated atria. (25th November 2020) - Kaba, R.A; Ashry, A; Elbadri, A; Gukop, P; Li, A; Sohal, M; Bajpay, A; Saba, M; Sharma, R.A; Gallagher, M; Chandrasekaran, V; Momin, A
Abstract: Introduction: Although catheter ablation therapy is a well-established treatment for cardiac dysrhythmias, the success rates for longstanding, persistent AF with dilated atria remain unsatisfactory. The minimally invasive hybrid technology is a novel form of therapy. Methods: A prospective, single-center UK study to evaluate the hybrid ablation technique for patients with longstanding (>1 year) persistent AF and dilated atria. Stage 1 was a minimally invasive epicardial approach for ablation of the posterior wall of left atrium (LA) and pulmonary veins (PVs). Stage 2 was a transcatheter approach via the femoral veins to isolate the endocardial aspect of the PVs +/− posterior wall. Occasionally, the sequence of the stages was reversed. Results: Forty-one patients were enrolled for the study with a mean follow-up for 16±9 months. Mean age was 65±9 years and the mean BMI was 32±7. Males constituted 75% of the study cohort. Mean LA size was 48±7 mm and mean left ventricular ejection fraction (LVEF) was 51.9%, although 51.6% of patients had impaired LVSF (LVEF below 55%). 87.8% CI (0.7–0.9) of patients remained in sinus rhythm (SR) without repeat ablation, whereas only 12.2% CI (0.04–0.02) had redeveloped persistent AF. Although numerically different, there was no statistically significant difference in maintaining SR between patients with severely dilated LA (>50 mm) and those without (70% vs. 90%, respectively; z=−1.39, p=0.165). Major perioperative complications during stage 1 ablation were low, with IVC injury in 1 patient and a mild stroke in 1 patient. Median LOS was 1 day (1–4 days) and there was no 30-day mortality after stage 1. Conclusions: The hybrid ablation therapy has a conversion rate from longstanding persistent AF to SR of 87.8% at a mean follow-up of 16±9 months, without repeat ablation. LOS was short, with very few complications and no peri-operative mortality. The hybrid approach appears to be very encouraging for a condition with otherwise low success rates by conventional endocardial techniques alone. Funding Acknowledgement: Type of funding source: None